Organisational performance, environmental management accounting practices and competitive advantage: evidence from Malaysia - Junainah Jaidi; Sarimah Samad; Raman Noordin; Rasid Mail; Thien, Sang Lim (2018)
In order to respond to the demand for the integration of environmental aspects of the corporate strategy, hotel managers’ belief that the practice of right management accounting practices is crucial. The management teams within the hotel industry believe that practising the right management accounting practices, termed as environmental management accounting (EMA), will lead to better organisational performance. They believe that the information produced by EMA will not only garner competitive advantage but will result in another outcome which is value creation. Grounded in the resource-based view, this study examined the relationship between EMA practices and organisational performance among Malaysian hotels. This research further examined the mediating role of competitive advantage on the link between EMA practices and organisational performance. Employing the simple random technique, the Partial Least Squares (PLS) approach to Structural Equation Model (SEM) was used to analyse data collected from 122 hotel managers from 3 to 5-star hotels in Malaysia. The findings of the hypothesis testing showed that all hypotheses were supported. Thus, it was concluded that there is a significant and positive relationship between EMA practices and organisational performance.